2021
DOI: 10.48550/arxiv.2112.15327
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sufficient Statistic Memory AMP

Abstract: Approximate message passing (AMP) is a promising technique for unknown signal reconstruction of certain highdimensional linear systems with non-Gaussian signaling. A distinguished feature of the AMP-type algorithms is that their dynamics can be rigorously described by state evolution. However, state evolution does not necessarily guarantee the convergence of iterative algorithms. To solve the convergence problem of AMPtype algorithms in principle, this paper proposes a memory AMP (MAMP) under a sufficient stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…It is proved that the SE of OAMP is convergent [41], [42]. Let (ρ * , v * ) with v * = φS SE (ρ * ) be the unique fixed point.…”
Section: Provides a Graphical Illustration Of (11)mentioning
confidence: 99%
“…It is proved that the SE of OAMP is convergent [41], [42]. Let (ρ * , v * ) with v * = φS SE (ρ * ) be the unique fixed point.…”
Section: Provides a Graphical Illustration Of (11)mentioning
confidence: 99%
“…Assumption 1: The entries of x are IID with zero mean. The variance of x is normalized, i.e., 1 N E{ x 2 } a.s.…”
Section: A Problem Formulationmentioning
confidence: 99%
“…We assume that M,N → ∞ with a fixed δ = M/N , and A is known and is right-unitarily-invariant, i.e., U Σ and V are independent, and V is Haar distributed (or equivalently, isotropically random). Furthermore, the empirical eigenvalue distribution of AA H converges almost surely to a compactly supported deterministic distribution with unit first moment in the large system limit, i.e., 1 N tr{AA H } a.s.…”
Section: A Problem Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Significantly, it was shown that any L-banded covariance matrix converges in [11], [13], [14], i.e., its diagonal en-tries converge (See Lemma 2). As a result, the convergence difficulties of general iterative algorithms were resolved in principle.…”
Section: Introductionmentioning
confidence: 99%